Last resort: case of clot translocation in intra-arterial stroke therapy. (15th January 2014) - John, Seby; Burgess, Richard; Cheng-Ching, Esteban; Wisco, Dolora; Taqui, Ather; Bain, Mark; Toth, Gabor; Uchino, Ken; Hui, Ferdinand; Hussain, Muhammad Shazam
Abstract : A patient was taken for emergent intra-arterial stroke therapy for an acute left middle cerebral artery stroke syndrome, with CT angiography showing a left internal carotid artery (ICA) occlusion. Through a 6 F Neuron MAX sheath, a 5 Max ACE Penumbra aspiration catheter was advanced to the thrombus and direct suction was performed through the ACE catheter and Neuron MAX sheath. Upon pull back, the thrombus became wedged in the Neuron MAX sheath and despite several attempts to aspirate the thrombus, no clot could be obtained. The Neuron MAX sheath was withdrawn to the left common carotid artery, and gently advanced to the origin of the external carotid artery (ECA). A glide wire was advanced and the thrombus dislodged into the ECA. Another pass with the 5 Max ACE was used to remove a remaining thrombus in the left ICA terminus, resulting in Thrombolysis in Cerebral Infarction (TICI) 3 flow. With improved devices for embolectomy, large and rigid emboli that exceed the inner diameter of large guide sheaths and balloon guide catheters can become lodged, and cannot be withdrawn through a catheter. While uncommon, strategies to overcome this are important to keep in mind during acute stroke intervention.